Enhanced Uranium Immobilization and Reduction by Geobacter sulfurreducens Biofilms - Cologgi, Dena L. (Appl Environ Microbiol, 2014)
Biofilms formed by dissimilatory metal reducers are of interest to develop permeable biobarriers for the immobilization of soluble contaminants such as uranium. Here we show that biofilms of the model uranium-reducing bacterium Geobacter sulfurreducens immobilized substantially more U(VI) than planktonic cells and did so for longer periods of time, reductively precipitating it to a mononuclear U(IV) phase involving carbon ligands. The biofilms also tolerated high and otherwise toxic concentrations (up to 5 mM) of uranium, consistent with a respiratory strategy that also protected the cells from uranium toxicity. The enhanced ability of the biofilms to immobilize uranium correlated only partially with the biofilm biomass and thickness and depended greatly on the area of the biofilm exposed to the soluble contaminant. In contrast, uranium reduction depended on the expression of Geobacter conductive pili and, to a lesser extent, on the presence of the c cytochrome OmcZ in the biofilm matrix. The results support a model in which the electroactive biofilm matrix immobilizes and reduces the uranium in the top stratum. This mechanism prevents the permeation and mineralization of uranium in the cell envelope, thereby preserving essential cellular functions and enhancing the catalytic capacity of Geobacter cells to reduce uranium. Hence, the biofilms provide cells with a physically and chemically protected environment for the sustained immobilization and reduction of uranium that is of interest for the development of improved strategies for the in situ bioremediation of environments impacted by uranium contamination.